Depression, Anxiety and Quality of Life Among Hematological Cancer Patients in Ampang Hospital - Das, Priscilla (2011)
Objectives: The present study was designed to determine the prevalence of major depressive disorder (MDD), anxiety disorders and other psychiatric disorders in hematological cancer patients. The study also investigates the socio-demographic profiles, hematological cancer diagnoses, clinical characteristics and psychosocial characteristics between patients with MDD or anxiety disorders and patients without the MDD or anxiety disorders. Methods: The research, which uses a cross sectional design with universal sampling, has been carried out at Ampang Hospital, Kuala Lumpur. The hospital is a tertiary referral center for cancer cases that include non-Hodgkin lymphoma, acute myelogenous leukemia, acute lymphoblastic leukemia, Hodgkin lymphoma and other hematological cancers. The study population consisted of all hematological cancer patients admitted to hematological wards during the sampling period between May 2009 and December 2009. The face to face interview questionnaire, MINI International Neuropsychiatric Interview was used in the study for diagnosis of MDD, anxiety disorder and other psychiatric disorders. The following self administered questionnaires were used: Patient Health Questionnaire (PHQ-9) for assessment of the severity of depressive symptoms, European Organization for Research and Treatment of Cancer Quality Of Life questionnaire (EORTC QLQ-C30) to assess the respondents’ quality of life, Brief Cope to examine coping styles, Visual Analog Pain scale to assess pain and Single Item Measure Support to determine the number of people willing to help patients. The Statistical Package for Social Sciences (SPSS) programme version 17.0 was used for data analysis and p <0.05 was set for statistical significance. Results: In total, 105 patients (100% response rate) with hematological malignancies were sucessfully included in the study. The prevalence of MDD was 24.8% (n=26), with the majority of the patients experiencing moderately severe depression (38.5%). About 92.3% (n=24) of depressed hematological cancer patients were diagnosed with a current episode of MDD. The depressed patients also had a significantly reduced quality of life in the physical, role, emotional, cognitive and social domains (p<0.05). They also had significantly more symptoms of fatigue, nausea and vomiting, dyspnoea, insomnia, appetite loss, constipation, diarrhea, financial difficulties and poor global health status (p<0.05). The MDD was correlated with global health status, physical functioning, role functioning, emotional functioning, cognitive functioning, social functioning, fatigue, nausea and vomiting, dyspnoea, insomnia, loss of appetite, constipation, diarrhea and financial difficulties (p<0.05). Significant factors related to MDD in terms of quality of life were social functioning, nausea and vomiting, insomnia and financial difficulties. The overall prevalence of anxiety disorders among the patients was 30.5% (n=32). Types of anxiety disorders include: agoraphobia without history of panic disorder (24.8%); generalized anxiety disorder (10.5%); social anxiety disorder (7.6%); panic disorder with agoraphobia (2.9%); post traumatic stress disorder (2.9%); obsessive compulsive disorder (1.9%) and panic disorder without agoraphobia (1%). Anxiety disorders significantly affected patients’ quality of life by altering the physical, emotional, role, and cognitive functions, insomnia, dyspnoea, nausea and vomiting, appetite loss and constipation (p<0.05) compared to patients without the disorder. In short, anxiety disorders were found to be correlated with quality of life. Among the subjects the suicidal ideations was found 2.9%, other psychiatric disorder: alcohol dependence, abused alcohol, substance abuse and anorexia nervosa were 1%, substance dependence was 1.9% and 4.9% had bulimia nervosa. The two most prevalent symptoms/problems among the hematological cancer patients were fatigue (79%; severe: 38%) and financial difficulties (74%; severe: 57%). We also found significant differences in patients’ employment statuses, monthly wages and types of hematological cancer diagnoses with quality of life in different domains. The four leading coping strategies employed by hematological cancer patients were behavioral disengagement (7.21%), active coping (6.44%), denial (6.32%) and venting (6.21%). The coping styles were found to be associated with MDD, socio-demographic profiles and clinical factors. Significant related factors to MDD were the self-distraction coping style and the positive reframing coping style. Conclusion: In brief, like other cancer patients, hematological cancer patients were also more likely to have psychiatric disorders such as depression, anxiety, other psychiatric disorders, reduced quality of life and poor coping styles. Special attention in psychotherapy should be provided to them to improve their quality of life together with their coping styles so that they may overcome their overall mental health problems.